Geographic and temporal variations in the incidence of vulvar and vaginal cancers. Issue 10 (6th July 2020) - Bray, Freddie; Laversanne, Mathieu; Weiderpass, Elisabete; Arbyn, Marc
Abstract: Vulvar and vaginal cancers are relatively rare cancers, together responsible for less than 1% of the global cancer incidence among women in 2018. The majority of vaginal cancers and a lesser proportion of vulvar cancers are associated with HPV, with rising incidence rates of vulvar cancer observed in younger women, possibly due to an increased prevalence of high‐risk HPV types. This report assesses recent international variations in the incidence rates of vulvar and vaginal cancer derived from high‐quality data from population‐based cancer registries in 68 countries, and further assesses time trends for selected longer‐term series in eight countries (Australia, China, Colombia, India, Norway, Slovakia, the U.S., and the U.K.) over the period 1983 to 2012. We observed a 30‐fold variation in the recorded incidence rates of vulvar cancer in contrast with the threefold variation for vaginal cancer. We also observed a rising incidence of vulvar cancer in Australia, Norway and the U.K., and Slovakia, with a more rapid rise in the rates seen in women aged < 60 years at diagnosis. The annual percentage change over the most recent decade varied from 1.7% in Norway to 4.1% in Slovakia. The increases are largely confined to younger women and are likely linked to generational changes in sexual behaviour (earlier age at sexual debut and increasing transmission of HPV among cohorts born 1940 to 1950 and thereafter. Vaginal cancer incidence rates, in contrast, were lower and more stable, despite the higher HPV‐attributable fraction relative to vulvar cancer. Irrespective of the trends, an increasing number of women are predicted to be diagnosed worldwide with both cancer types in future decades as population ageing and growth continues. The promise of high‐coverage HPV vaccination will likely counter this rising burden, but the impact may take a number of decades. Abstract : What's new? Vulvar and vaginal cancer incidence varies geographically, and although relatively rare, in some areas incidence may be increasing alongside changes in the prevalence of human papillomavirus (HPV) infection. Here, the assessment of trends in vulvar and vaginal cancer incidence in geographically diverse countries reveals increasing incidence of vulvar cancer in women under age 60 in several populations. By comparison, despite a higher HPV‐attributable fraction, vaginal cancer incidence was lower and more stable. Increasing oncogenic HPV infection will likely raise the incidence of these cancers as populations age and grow, though this effect may be countered over the long‐term by HPV vaccination.